Simultaneous Determination of Six Active Compounds in Yixin Badiranjibuya Granules, a Traditional Chinese Medicine, by RP-HPLC-UV Method - Ning Yu; ChenHui He; Gulistan Awuti; Cheng Zeng; JianGuo Xing; Wei Huang (Journal of Analytical Methods in Chemistry)
In this study, a sensitive, precise, and accurate HPLC-UV method was developed and validated to simultaneously determine the six analytes (luteolin-7-O-β-D-glucuronide, apigenin-7-O-β-D-glucuronide, diosmetin-7-O-β-D-glucuronide, acacetin-7-O-β-D-glucuronide, tilianin, and rosmarinic acid) in Yixin Badiranjibuya Granules, in which five analytes (i.e., luteolin-7-O-β-D-glucuronide, apigenin-7-O-β-D-glucuronide, diosmetin-7-O-β-D-glucuronide, acacetin-7-O-β-D-glucuronide, and rosmarinic acid) were determined for the first time in Yixin Badiranjibuya Granules, the content of tilianin in Yixin Badiranjibuya Granules was reported in other literatures, and the content of tilianin in our work was higher than that of the literature reports. The quality of 11 batch samples from four different manufacturers was evaluated using the proposed determination method. The contents of the six analytes were largely different among samples from various manufacturers. Therefore, this determination method can provide a scientific basis for quality evaluation and control of Yixin Badiranjibuya Granules.